Energy efficient hourly scheduling of multi-chiller systems using imperialistic competitive algorithm. (March 2020) - Jabari, Farkhondeh; Mohammadpourfard, Mousa; Mohammadi-ivatloo, Behnam
Highlights: ICA is used for solving optimal chiller loading problem and saving energy. Robustness and effectiveness of ICA is proved using simulations on three well-known test systems. ICA based optimization process is compared with recently published methods. ICA with fast convergence capability achieves better solutions in lower calculation time. Abstract: The hour-ahead optimization of the multi-chiller systems is necessary in order to minimize their power consumption and save energy. In this paper, an imperialistic competitive algorithm based optimal chiller loading problem is solved to find the partial load ratio, cooling flux, and the electricity requirement of the chillers and minimize the energy consumption of the whole system. The proposed approach simulates the socio-political competition using the initial population composed of the colonies and imperialists. The empires with their relative colonies and imperialists compete with each other to collapse the weakest empire and dominate the most powerful one achieving the minimum power consumption. The cooling capacity of the chillers and balance constraint are satisfied in hourly economic dispatch process. The optimization problem is tested on three standard systems. The imperialistic competitive algorithm based optimal chiller loading method finds better operating points for chillers than those obtained by recently published strategies.